2015
DOI: 10.1177/0956797615569580
|View full text |Cite|
|
Sign up to set email alerts
|

Popularity, Similarity, and the Network Extraversion Bias

Abstract: Using the emergent friendship network of an incoming cohort of students in an M.B.A. program, we examined the role of extraversion in shaping social networks. Extraversion has two important implications for the emergence of network ties: a popularity effect, in which extraverts accumulate more friends than introverts do, and a homophily effect, in which the more similar are two people's levels of extraversion, the more likely they are to become friends. These effects result in a systematic network extraversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(113 citation statements)
references
References 38 publications
6
106
0
1
Order By: Relevance
“…It is likely that extraverts will engage in higher amounts of social activity on SNS because they are reward seeking and sociable. Prior studies on SNS have consistently found that extraverts not only spend more time on SNS (Wilson, Fornasier, and White, 2010), had more Facebook friends (Ong et al, 2010;Ross et al, 2009), and also are central in many social networks (Feiler & Kleinbaum, 2015).…”
Section: The Big Five Traits and Social Network Sites Usementioning
confidence: 99%
“…It is likely that extraverts will engage in higher amounts of social activity on SNS because they are reward seeking and sociable. Prior studies on SNS have consistently found that extraverts not only spend more time on SNS (Wilson, Fornasier, and White, 2010), had more Facebook friends (Ong et al, 2010;Ross et al, 2009), and also are central in many social networks (Feiler & Kleinbaum, 2015).…”
Section: The Big Five Traits and Social Network Sites Usementioning
confidence: 99%
“…It is made available under a The copyright holder for this preprint (which was not . http://dx.doi.org/10.1101/098988 doi: bioRxiv preprint first posted online Jan. 9, 2017; encode extraversion 22 , which is modestly correlated with EC 25 , suggesting that this region may encode dispositional tendencies common to both extraversion and EC. In addition, recent work has also shown that the medial parietal cortex, as well as other regions involved in inferring others' mental states, intentions, and traits (e.g., MPFC; temporoparietal junction), responds preferentially to well-liked individuals, which is thought to reflect perceivers being preferentially motivated to understand the internal states of popular others 26 .…”
Section: Cc-by-nc-nd 40 International License Peer-reviewed) Is the mentioning
confidence: 99%
“…Who comes to occupy these central network positions? Recent research suggests that individuals' personalities influence their ability to attract social ties (6)(7)(8)(9)(10)(11),* but this personality-centrality relationship may vary depending on the type of connection that one uses to define a network. For example, extraverts become more central than introverts in networks defined by friendship (6).…”
mentioning
confidence: 99%